Agroecology for sustainable development: evidence on multidimensional performance from a cross-country TAPE assessment in Africa - Adoyo, Beatrice; Geck, Matthias S.; Adeyemi, Chabi; Alpuerto, Joe; Arinloye, Ademonla A. Djalalou-Dine; Ateku, Dickens; Autfray, Patrice; Barahona, Carlos; Chacha, Robin; Cluset, Rémi; Innocent, Faith; Karari, Valentine; et al. (Frontiers in Sustainable Food Systems, 2025)
IntroductionAgroecology is increasingly recognized as a pathway for transforming agrifood systems and advancing progress toward the SDGs. Yet, large-scale, cross-context evidence on its multidimensional performance as framed holistically by the FAO’s 10 Elements remains limited.MethodsThe Tool for Agroecology Performance Evaluation (TAPE) and the Land Degradation Surveillance Framework (LDSF) were applied on 839 farming households in Benin, Ethiopia, Kenya, and Madagascar. Correlation analysis was used to quantify relationship between agroecological integration and multidimensional performance key drivers were identified through regression analysis.Results and DiscussionHigher levels of agroecological integration are significantly positively correlated with higher performance across economic, environmental and social domains. This implies that the environmental benefits of agroecology do not come at the cost of reduced productivity and profitability and suggests that agroecology significantly contributes to sustainable development in Africa. Sociocultural Elements of Agroecology, including human and social values, culture and food traditions, and knowledge co-creation, emerged as key drivers of agroecological transitions and multidimensional performance. However, barriers remain, such as high input costs, insecure land tenure (particularly for women), and low youth engagement in farming. The study emphasizes the need for enabling policies that support agroecological business models, secure tenure rights, and foster equitable, labor-saving innovations. By providing multi-country evidence, it underscores the value of systemic, holistic food system assessments to guide agroecological transitions.